Performance of a Single-Cylinder Four-Stroke Engine with High Concentrations of Gasoline-Ethanol-Methanol (GEM) - M Hanifuddin; Muhammad Faja Taufiqurrahman; Tri Aji Setyawan; Riesta Anggarani; Cahyo Setyo Wibowo; Bambang Sugiarto (Universitas Muhammadiyah Magelang, 2023)
Several types of alternative fuels have been developed to replace fossil fuels. Alcohols, such as ethanol and methanol, can be blended with gasoline for spark ignition (SI) engines. High octane number and oxygen content in alcohol can increase combustion efficiency. Therefore, our current research investigates the effect of high concentrations of ethanol and methanol mixed in 90 RON gasoline. The mixture was implemented in a 150 cc single-cylinder four-stroke spark ignition (SI) engine without any modifications. Engine testing was carried out with wide-open throttle (WOT) and different engine speeds from 4000 to 10000 rpm. Torque, power, and Air Fuel Ratio (AFR) were measured during experiments on a chassis dynamometer. Our test results found that the higher the methanol fraction in the mixture, the lower the torque generated. To improve engine performance, further research is needed on modified engines so that optimal conditions can be identified.